Satisfying thirst - the problem of water in terms of health education and health promotion - Izabella Maria Łukasik (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Ecological models of health behaviour, which are entangled in environmental and political contexts of behaviour and underpinned by social and psychological influences, have been used in health promotion for many years. It seems that it is worth to use them to develop health awareness related to the problem of water availability. Three elements are important here. The first concerns the recognition of the scarcity of water resources, especially drinking water. The second important element is the safe sources of water used for consumption, hygiene and sanitation. The third component is proper hydration and its benefits. Current information on this is provided by agencies such as the WHO, UNICEF, and the reports produced are available on the Internet. The state of water is not satisfactory and the culture of drinking and using water for hygiene purposes is still a cause for concern. It is therefore necessary that measures taken to improve the situation in this field be monitored.